2008
DOI: 10.3928/01477447-20081201-01
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spine Injury: Tiger Attack

Abstract: Many intra-articular fracture patients eventually experience significant functional deficits, pain, and stiffness from post-traumatic osteoarthritis (PTOA). Over the last several decades, continued refinement of surgical reconstruction techniques has failed to markedly improve patient outcomes. New treatment paradigms are needed - ideally, bio/pharmaceutical. Progress in that direction has been impeded because the pathomechanical etiology of PTOA development is poorly understood. In particular, the relative ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…We have shown that explants in our model system undergoing healthy or injurious loading demonstrated no aberrant mechanical behavior indicative of structural failure over the course of any experiment. Overall axial strains after 3 hours of cyclic compression with 1.0 MPa (40-50%) were clearly elevated above estimates of in vivo strains in normal joints (10-15%) [1,2,4,22]. However, it is possible that contact stress elevations associated with unstable or incongruent joints, or normal contact stresses on degenerated cartilage lead to strain values in the range we imposed by 1.0 MPa compression in our system [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that explants in our model system undergoing healthy or injurious loading demonstrated no aberrant mechanical behavior indicative of structural failure over the course of any experiment. Overall axial strains after 3 hours of cyclic compression with 1.0 MPa (40-50%) were clearly elevated above estimates of in vivo strains in normal joints (10-15%) [1,2,4,22]. However, it is possible that contact stress elevations associated with unstable or incongruent joints, or normal contact stresses on degenerated cartilage lead to strain values in the range we imposed by 1.0 MPa compression in our system [22].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have shown that individuals in occupations involving heavy repetitive loading of their joints as well as elite athletes are at increased risk for developing OA [1,2; reviewed 3,4]. Studies suggest that manipulations of key factors including surface mechanics, inflammation, or oxidative injury can alleviate different aspects of cellular injury from overloading [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to that for bites from their smaller domestic relatives, Pasteurella infection is a high risk for bites from large cats, including lions, tigers, cougars, and others (159,162,164,166,293,(371)(372)(373)(374)(375). Cases of Pasteurella infections have also been reported for bites or exposure to mucous secretions from other wild and domestic animals, including rats, opossums, horses, and rabbits (166,259,287,295,376).…”
Section: Rare Cases Of Zoonotic Transmission Through Wild Animalsmentioning
confidence: 99%
“…Reported cases of attacks on humans by the tigers are very rare in the world [1][2][3][4][5][6][7]. At present, amongst the very few reported cases in the medico-legal literature, there are only three cases of fatal tiger attacks, where the victims have died due to the tiger bite injuries resulting from the known method of tiger attack [1][2][3].…”
Section: Introductionmentioning
confidence: 98%